SQUAMOUS CELL CARCINOMA OF THE HEAD AND NECK: NEW AVENUES OF TREATMENT? - T. Braunschweig; A. Lewandrowski; D. Smeets; M. V. Bolotin (Опухоли головы и шеи)
Squamous cell carcinoma of the head and neck counts for 3 % of all cancers in men and half of this number less in women with a 5-year survival of 61 %. While the number of laryngeal carcinoma is decreasing, carcinoma of the oral cavity related to an infection by the human papilloma virus (HPV), high-risk subtypes is increasing, especially in younger patients. HPV related squamous cell carcinomas show better survival data, especially in regard to recurrence free rates or secondary carcinoma of adjacent locations. Squamous cell carcinomas related to the presence of HPV DNA material is almost exclusively found in carcinoma of the oral cavity and oropharyngeal mucosa. Much less frequently HPV is present in hypopharyngeal carcinomas and even less number of cases of squamous cell carcinoma with proof for HPV in the nasopharynx and larynx. In case of evidence for HPV DNA; most cases are positively tested for subtype 16, followed by subtype 18. As a surrogate immunhistochemical marker, p16 INK4A is stained positive, cytoplasmic and nuclear. In a small study by ourselves, we found a positive correlation in 100 % of p16 INK4A positivity and positive HPV testing. Oral squamous cell carcinoma is more frequently related to HPV in patients below 50 years of age with a prevalence of ca. 20 %. Whilst HPV high-risk positive carcinomas show very few mutations in single signalling molecules of the downstream receptor tyrosin kinase pathways, HPV negative carcinomas show in many cases a chaotic DNA mutation type with typical mutations in tumor suppressor genes, as p53 and CDKN2A. This pattern is often seen in carcinoma types develop from a summation of accidental mutations often caused by toxins (e.g. inhaled cigarette smoke). However, it is discussed and under investigation whether a subset of head and neck squamous cell carcinomasdevelop from so called driver mutations, as are called mutations in critical members of signalling pathways and receptor tyrosin kinases, e. g. FGF receptors, PTEN, PIK3CA. In a similar group of squamous cell carcinomas, those of the lower airways, trachea, bronchi and lung parenchyma, also massively caused by inhaled toxins, a subset of 20 % show these driver mutations. Tumors with driver mutations, especially related to tyrosin kinases and depending pathways are eligible for small molecule therapeutics, inhibitors of tyrosin kinases and signalling kinases, e. g. Erlotinib in EGF receptor or Vemurafininb for B-RAF. There is much need for further stratification of head and neck squamous cell carcinoma to introduce the wide field of inhibitors at least to a subset of these patients.